Chronic fatigue syndrome/myalgic encephalomyelitis in children aged 5 to 11 years: A qualitative study. (January 2021) - Brigden, Amberly; Shaw, Alison; Anderson, Emma; Crawley, Esther
Treatments for paediatric chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) have not been designed or evaluated for younger children (5–11-years). The development of a complex intervention for this population requires an in-depth understanding of the perspectives and psychosocial context of children and families. Children with CFS/ME (5–11-years) and their families were recruited from a specialist CFS/ME service, and interviewed using semi-structured topic guides. Data were analysed thematically. Twenty-two participants were interviewed; eight parents, two children (aged nine and ten) and six parent-child dyads (aged 5–11-years). Theme 1: CFS/ME in younger children is complex and disabling. Theme 2: Children aged eight and over (in comparison to those under eight) were more able to describe their illness, engage in clinical consultation, understand diagnosis and self-manage. Theme 3: Parents of children under eight took full responsibility for their child's treatment. As children got older, this increasingly became a joint effort between the parent and child. Parents felt unsupported in their caring role. Clinicians should consider different treatment approaches for children under eight, focusing on: parent-only clinical sessions, training parents to deliver treatment, and increasing support for parents. Children over eight may benefit from tools to help them understand diagnosis, treatment and aids for self-management.